Evaluation of the Implementation of the Mining Safety Management System (SMKP) and Safety Culture in the Maintenance Department of PT Bumi Suksesindo - Sukadi Sukadi; Hairrudin Hairrudin; Isa Ma'rufi (Poltekkes Kemenkes Palu, 2023)
Occupational accidents in Indonesia's Mineral and Coal (Minerba) mining sector are still quite high. In 2022, there were 11 of 93 cases of fatality accidents. Organizational factors that often become the basic cause of accidents are the non-optimal implementation of the work safety management system and the low level of Safety Culture. The mining safety management system (SMKP) has been implemented at PT Bumi Suksesindo, but the number of accidents was still high, namely 16 accidents in the Maintenance department in 2022. This study aims to evaluate the implementation of SMKP and the maturity level of OSH culture (safety culture) in the Maintenance department. This was an evaluation study with a descriptive approach. Data were collected using a questionnaire and document review. The number of samples was 140 of 214 population of field workers. A 5-point Likert scale was applied to analyze workers' perceptions of the implementation of SMKP. The causal factors were analyzed using Incident Cause Analysis Methodology (ICAM), while the evaluation of the Safety Culture level was performed through a frequency distribution based on the 5 levels of OSH culture in accordance with UK CoalJourney, namely Basic, Reactive, Planned, Proactive, Resilient. The implementation rate of the Mining Safety Management System (SMKP) in the Maintenance department of PT Bumi Suksesindo was 67%, which was included in the Good category. However, there were 16 occupational accident cases, and the organizational factor was the most common cause (45 findings). Furthermore, the OSH culture maturity level was 60.5%, included in the Resilient level. It can be concluded that the implementation of SMKP in the Maintenance department was still sub-optimal, and the OSH culture maturity level had not yet covered 100% of workers. Such a finding implies a high number of occupational accidents. It is necessary to supervise the implementation of the SMKP and plan an OSH culture improvement program by involving all workers to achieve the SMKP goal of preventing occupational accidents.